Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik - Ingold, Niklaus; Ochsner, Peter E.; Steinke, Hubert (2023)
The implantation of artificial hip joints to treat painful osteoarthritis is considered a twentieth-century medical success story. Between 1960 and 1990, orthopedists and surgeons transformed joint replacements from an experimental procedure to a routine operation. One of the protagonists was Swiss doctor Maurice E. Müller, who replaced a complete hip joint with metal and plastic components for the first time on mainland Europe in February 1961. But he did not act alone. People with a wide range of skills were involved in the development, manufacture, and establishment of artificial hip joints, including mechanics, materials scientists, engineers, production managers, managers, training coordinators, and database specialists.Based on interviews with contemporary witnesses, the book reveals the network that made it possible to enter new medical technology in Switzerland in the pioneering era. The images are not covered by the CC BY license.Copyright © of the images by the photographers and archives.